Diagnosis and management of oral cavity lipoblastoma and lipoblastomatosis in an 8‐month‐old boy. Issue 9 (30th August 2021) - Matous, Allison L.; Baker, Michael L.; Khan, Rihan; Pastel, David A.; Chen, Eunice Y.
Abstract: Lipoblastoma/lipoblastomatosis presents some unique diagnostic and therapeutic challenges when encountered in the oral cavity. In these rare cases, diagnostic confirmation with molecular testing and a conservative surgical resection can contribute to successful management. Abstract : Lipoblastoma/lipoblastomatosis presents some unique diagnostic and therapeutic challenges when encountered in the oral cavity. In these rare cases, diagnostic confirmation with molecular testing and a conservative surgical resection can contribute to successful management.